Comparison of Nitrate Content in Smooth Cayenne Pineapple Flesh Related to Its Different Cut Sections, Maturity and Crop Season - Sasathorn Srivichien (My University, 2014)
High nitrate (NO 3 ) level in pineapple flesh affected to cans.It is one of main problems in pineapple canning factory.Pineapple with high NO 3 content is required to screen out before feeding to a process of the factory.Knowledge of NO 3 content in pineapple is important for quality control due to checking of NO 3 content in pineapple is random.There is still no scientific evidence to support what a suitable procedure for nitrate inspection should be handled.Therefore this is research was aimed to study the level of nitrate in difference part of pineapple fruit (top, middle and bottom) related to maturity stage and crop seasons.A batch of 82 pineapple fruits (harvested in summer and rainy season) was used in this research.Each sample was divided into 3 parts (top, middle and bottom).The amount of nitrate in each part of pineapple flesh was determined by HPLC.By statistical analysis, the level of nitrate at different cut sections of pineapple flesh was no significant difference.The nitrate level of pineapple flesh with lower brix and acid ratio (B/A<23) was significantly different to those of flesh with higher brix and acid ratio (B/A>23).The nitrate level of pineapples flesh harvested in summer season was significantly different to those of flesh harvested in rainy season.Therefore, NO 3 content in pineapple wasn't related to cut section but it was related to maturity and crop season.
Keywords: Flesh; Pineapple and bromelain studies